2019
DOI: 10.1007/s40333-019-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation of soil moisture in a fixed dune at the southern edge of the Gurbantunggut Desert in Xinjiang, China

Abstract: Soil moisture is critical for vegetation growth in deserts. However, detailed data regarding the soil moisture distribution in space and time in the Gurbantunggut Desert of China have not yet been reported. In this study, we conducted a series of in situ observation experiments in a fixed sand dune at the southern edge of the Gurbantunggut Desert from February 2014 to October 2016, to explore the spatio-temporal variation of soil moisture content, investigate the impact of Haloxylon ammodendron (C. A. Mey.) Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Lal (2013) and López-Bellido (2015) mentioned that the use of waste mulch and other biosolids is a technique for turning soil into a carbon sink, reducing GGE. The availability of water exerts a strong influence on the development of vegetation cover (Zhu et al, 2019). Gambetta et al (2015) evaluated the application of lime as a mechanical cover in mandarin varieties Satsuma and Clementina and found that the STe decreased by between 0.5 and 3°C.…”
Section: Soil Coversmentioning
confidence: 99%
“…Lal (2013) and López-Bellido (2015) mentioned that the use of waste mulch and other biosolids is a technique for turning soil into a carbon sink, reducing GGE. The availability of water exerts a strong influence on the development of vegetation cover (Zhu et al, 2019). Gambetta et al (2015) evaluated the application of lime as a mechanical cover in mandarin varieties Satsuma and Clementina and found that the STe decreased by between 0.5 and 3°C.…”
Section: Soil Coversmentioning
confidence: 99%
“…Soil moisture is highly variable over time and space, which is known as spatio-temporal variability. This variability exerts a strong influence on the development of vegetation cover, which is crucial when analyzing all related processes in the soil-plant-atmosphere interaction (Zhu et al, 2019).…”
mentioning
confidence: 99%